2020
DOI: 10.1111/ped.14286
|View full text |Cite
|
Sign up to set email alerts
|

Novel variants in Turkish patients with glycogen storage disease

Abstract: Background: Glycogen storage diseases (GSD) are disorders of autosomal recessive carbohydrate metabolism, characterized by glycogen accumulation. The liver and muscle tissue are commonly affected but patients may present with different clinical manifestations. The presence of glycogen can be demonstrated in biopsies and definitive diagnosis can be made by enzymatic or molecular analysis. The aim of this study was to determine specific gene mutations in our cases with GSD. Methods: Thirty-eight patients with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In a cohort of Iranian, GSD III ( AGL ), GSD IX ( PHKB and PHKG2 ) was the major type of GSD ( Beyzaei et al, 2021 ). In Turkish, the genetic analysis showed that the highest proportion of GSDs was type III with 39.5% (n = 15), followed by type I with 36.8% (n = 14) ( Cakar et al, 2020 ). While in Spain, Vega et al reported that more than three-quarters of patients with GSDs were type III or IXα ( Vega et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of Iranian, GSD III ( AGL ), GSD IX ( PHKB and PHKG2 ) was the major type of GSD ( Beyzaei et al, 2021 ). In Turkish, the genetic analysis showed that the highest proportion of GSDs was type III with 39.5% (n = 15), followed by type I with 36.8% (n = 14) ( Cakar et al, 2020 ). While in Spain, Vega et al reported that more than three-quarters of patients with GSDs were type III or IXα ( Vega et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Asian, c.1735 + 1G > T shows the highest frequency in Japanese, Korean and Chinese patients [ 20 ]. The common variant in Turkish patients is p. W1327X [ 21 ]. Despite these, there is still high heterogeneity of AGL variants worldwide and pathogenic variants scattered throughout the gene [ 22 ].…”
Section: Discussionmentioning
confidence: 99%